Programa de uso ético de la inteligencia artificial para mejorar la integridad académica en estudiantes de sexto ciclo de educación primaria en la Facultad de Ciencias de la Educación y Humanidades Iquitos 2024 - Lopez Vasquez, Ana Rosana (2025)
This study aimed to evaluate the effect of the ethical use of artificial intelligence program to improve academic integrity in sixth-year primary school students at the Faculty of Education Sciences and Humanities -FCEH- Iquitos 2024, using a quantitative evaluative approach with a quasi-experimental, field-based, longitudinal, and univariate design. A total of 70 students were sampled, distributed into an experimental group and a control group, selected through intentional non-probability sampling. The intervention, developed over 12 weeks in the experimental group, was evaluated using a standardized test administered before and after its implementation. The analyses conducted indicate that the implementation of the ethical use of artificial intelligence program had a highly significant impact on improving the academic integrity of sixth-grade students at the FCEH. Given that p-value = 0.001 < 1% (α = 0.01), the null hypothesis was rejected, and the alternative hypothesis was accepted at a confidence level of 99.9%. Improvements were also found in both the overall average and each of the five academic dimensions (academic honesty, responsibility, transparency, respect, and equity), confirming the program's effectiveness as a training strategy for strengthening students' academic ethics.